TEKNOLOGI PENGOLAHAN MOL (MIKROORGANISME LOKAL) WHEY KEFIR DAN LIMBAH PETERNAKAN SAPI POTONG DI NAGARI SUNGAI KAMUYANG, KABUPATEN LIMA PULUH KOTA - Ferawati Ferawati; Yulianti Fitri Kurnia; Reswati Reswati; Erpomen Erpomen; Khalil Khalil (LPPM Universitas Andalas, 2019)
This program is done to overcome the problems that occur in folk farmers and farmer groups in Sungai Kamuyang. Through discussions conducted with the community and the head of farmer groups facilitated by the headman of Sungai Kamuyang, the teams formulated several problems. Livestock waste that has not undergone maximum processing such as cow feces, urine and feed residue. Livestock waste is bulky and voluminous so that the use of the room is wide enough for storage and a disturbing aroma. The difficulty of obtaining forage, especially in the dry season and the low production of cultivated grasses planted by farmers around their cattle sheds, and the lack of skills of farmers in processing livestock waste is a problem that also occurs. Through this program, a solution was given, namely the creation of kefir Local Microorganism (LoM) by utilizing the remaining food and feces and urine of livestock through training and application of to cultivated grass. The final stage is to discuss the future marketing strategy for fertilizer as additional income for farmers. The purpose of this service was to increase the knowledge and skills of partner farmers in making Local Microorganism (LoM) as compost decomposers made from livestock waste, increase forage production through LoM based fertilization and increase farmers' income through selling LoM or decomposer compost using LoM. This program has given a progress to the pattern of people's livestock in Sungai Kamuyang.